EFFECT OF CHOLESTEROL BLOOD LEVEL REDUCTION BEGINNING EARLY IN LIFE ON THE RISK OF ISCHEMIC HEART DISEASE - N. V. Perova (Столичная издательская компания, 2015)
Comments to the paper B.A. Ference, et al. Effect  of Long-Term Exposure to Lower Low-Density Lipoprotein Cholesterol Beginning Early in Life on the Risk of Coronary Heart Disease. A Mendelian Randomization Analysis (translation is published in №1 2013:90-98)